Recognising influence: helping authors of non-traditional research outputs evidence the reach and potential impacts of their work - Bucknell, Terry (Septentrio Conference Series, 2016)
New technologies and the underlying scholarly structure mean that it is now easier than ever to track and report on the online activity surrounding scholarly articles. But how can these methods and tools be adapted to provide similar benefits for scholars who do not consider the journal article their primary form of output, and what challenges are associated with that? This poster will present some of the early developments in this area, and detail how the data might bring future benefits for researchers in a variety of disciplines.